Diffusion in two-component quasiparticle systems of liquid and solid mixtures of helium isotopes - Adamenko, I.N.; Nemchenko, K.E.; Zhukov, A.V.; George, T.F.; Pandey, L.N.; Um, Chung-In (Condensed Matter Physics, 1999)
An exact expression for the diffusion time which depends on the interaction rates for particles of not only different, but also of the same species,
has been derived from the system of kinetic equations. The result is valid
for particles with arbitrary statistics and energy-momentum relations. The
derived general relations are valid for investigating diffusion in liquid and
solid ³He-⁴He mixtures. The contribution of interaction between quasiparticles of the same type to the diffusion coefﬁcient and effective thermal
conductivity of superﬂuid solutions is analyzed. The calculated values are
compared with experimental data. The calculated diffusion coefﬁcient of
³He-⁴He solid solutions differs from the previous theoretical results. A comparison of the obtained diffusion coefﬁcient with experimental data makes
it possible to determine the numerical value of the energy band width for
impurity quasiparticles. Виходячи з системи кiнетичних рiвнянь для компонент сумiшi отримано точний вираз для дифузiйного часу, що залежить вiд взаємодiї
частинок не тiльки рiзних, а й одного типу. Отриманий результ справедливий для частинок з довiльною дисперсiєю і статистикою. Одержаний точний вираз використовується для дослiдження дифузiї у рiдких та твердих квантових розчинах ³He-⁴He. Проаналiзовано внесок взаємодiї мiж квазiчастинками однакових типiв у коефiцiєнт дифузiї та теплопровiдностi надплинних розчинiв. Обчисленi результати порiвнюються з iснуючими експериментальними даними. Отриманий коефiцiєнт дифузiї для твердих квантових розчинiв ³He-⁴He
iстотно вiдрiзняється від попереднiх результатiв теорiї. Порiвняння
цього результату з експериментальними даними дозволило дiстати
числове значення для енергетичної зони квазiчастинок домiшки.